The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4081/aiua.2022.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of urinary biomarkers of female bladder outlet obstruction (fBOO)

Abstract: Objective: Diagnosis of bladder outlet obstruction (BOO) in females is often challenging, not only because of the overlap in storage and voiding symptoms in women with various etiologies of lower urinary tract (LUT) dysfunction but also due to the lack of standardized urodynamic criteria to define the condition. There is an unmet need of biologic markers to evaluate BOO in females as an adjunct to other clinical criteria. We sought to elucidate the role of urinary biomarkers in female BOO. Material and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Urinary proteins had long been considered to have a diagnostic role in bladder dysfunction or bladder outlet dysfunctions [ 4 , 5 , 7 , 8 ]. However, owing to variations in urine collection, different renal conditions, and medical comorbidities, urine levels of biomarkers varied widely in the studies of OAB, IC/BPS, and DV-related BOO [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary proteins had long been considered to have a diagnostic role in bladder dysfunction or bladder outlet dysfunctions [ 4 , 5 , 7 , 8 ]. However, owing to variations in urine collection, different renal conditions, and medical comorbidities, urine levels of biomarkers varied widely in the studies of OAB, IC/BPS, and DV-related BOO [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urine contains proteins and is excreted from the kidney or bladder wall. Previous studies have found that some urinary cytokines, chemokines, and oxidative stress biomarkers are elevated in patients with overactive bladder (OAB), DO, IC/BPS, and DV [ 4 , 5 , 6 , 7 , 8 ]. Although urine-based biomarkers may provide valuable diagnostic and prognostic tools for the clinical assessment of LUTDs and treatment guidelines, the urine proteins currently found in women with different bladder disorders varied widely and are poorly reproducible [ 9 ].…”
Section: Introductionmentioning
confidence: 99%